1996
DOI: 10.1152/ajpcell.1996.270.5.c1311
|View full text |Cite
|
Sign up to set email alerts
|

cGMP produced in response to ANP and CNP regulates proliferation and differentiation of osteoblastic cells

Abstract: The effects of natriuretic peptides on the proliferation and differentiation of osteoblast-like cells from rat calvariae were examined. Natriuretic peptides are physiological agonists that activate receptor guanylate cyclases, namely, natriuretic peptide receptor (NPR)-A and NPR-B. Exposure of cells to atrial natriuretic peptide (ANP) and C-type natriuretic peptide (CNP) resulted in large increases in the rate of intracellular production of guanosine 3',5'-cyclic monophosphate (cGMP). Moreover, CNP-like immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 27 publications
5
76
0
Order By: Relevance
“…[21][22][23][24][25][26][27] In the OE, CNP is expressed in the distal processes and footpads of the sustentacular cells, positioning it to act on a variety of neuronal precursors. 16 Its receptor, guanylyl cyclase B (GC-B), is expressed within the basal layer of the OE and in more mature OSNs.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] In the OE, CNP is expressed in the distal processes and footpads of the sustentacular cells, positioning it to act on a variety of neuronal precursors. 16 Its receptor, guanylyl cyclase B (GC-B), is expressed within the basal layer of the OE and in more mature OSNs.…”
Section: Introductionmentioning
confidence: 99%
“…Over and above actions in chondrocytes, in vitro studies in rodents show that CNP transcripts are present in cells of osteoblast lineage (Suda et al 1996(Suda et al , 1999 and that CNP production from these cell lines can be augmented by TGFb (Suda et al 1996). Further the addition of CNP to murine preosteoblasts, acting via NPR-B and cGMP, inhibits cell proliferation while enhancing differentiation and markers of osteoblast maturation (ALP and osteocalcin; Hagiwara et al 1996). CNP also increases the formation of mineralised nodules.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) CNP stimulates the differentiation of osteoblastic lineage cells through its specific receptor, B-type natriuretic peptide receptor (NPR-B). [3][4][5] The targeted disruption of the genes coding for CNP 6) and NPR-B 7) causes dwarfism due to an impaired longitudinal growth of long bone, while the transgenic overexpression of CNP causes skeletal overgrowth, 8) suggesting that the CNP/NPR-B signaling pathway has an essential role in the regulation of bone metabolism. Recently, we have shown that the activation of CNP/NPR-B signaling causes the enhancement of bone for- * To whom correspondence should be addressed: Faculty of Pharmaceutical Sciences, Toho University, 2-2-1 Miyama, Funabashi, Chiba 274-8510, Japan.…”
Section: Introductionmentioning
confidence: 99%